Selected Papers from the 16th International Symposium on Magnetic Bearings (ISMB16) - Zhou, Jin; Wu, Huachun; Ueno, Satoshi; Sun, Feng (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
In 2018, the 16th International Symposium on Magnetic Bearings (ISMB16) was held in Beijing, China. Herein, eight distinguished papers were selected to be published as Special Issues of Actuators. These papers are suggested to provide new insights for the development of magnetic bearings, with emphasis on thermal behavior analysis, electrodynamic thrust bearings analysis, viscoelastic damping design, magnetic spring, condition monitoring, self-bearing motors performance.